A thick lithium iron phosphate electrode and its preparation method and application

By using a layered structure and conductive agent matching mode in the lithium iron phosphate thick electrode, a three-dimensional conductive network is formed, and the problem of difficult compatibility of energy density, rate performance and peel strength in the prior art is solved, and a thick electrode with high energy density, excellent rate performance and good cycle performance is achieved.

CN115394961BActive Publication Date: 2025-04-29EVE POWER CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210981616.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-15
Publication Date
2025-04-29
Estimated Expiration
2042-08-15

Smart Images

  • Figure CN115394961B_ABST
    Figure CN115394961B_ABST
Patent Text Reader

Abstract

The present invention provides a thick lithium iron phosphate electrode and a preparation method and application thereof. The thick lithium iron phosphate electrode includes a current collector and an electrode coating located on the surface of the current collector, the electrode coating includes a first coating and a second coating arranged in a stacked manner, wherein the second coating is located on the side close to the current collector, the first coating includes spherical lithium iron phosphate secondary particles, a first conductive agent and a first binder, and the second coating includes lithium iron phosphate single particles, a second conductive agent and a second binder. The present invention uses a layered structure of upper lithium iron phosphate secondary particles and lower lithium iron phosphate single particles (the upper layer is far away from the current collector) by matching active materials in the first coating and the second coating, which significantly reduces the tortuosity and liquid phase resistance, and forms larger pores between the spherical secondary particles, and smaller pores in the single particles, which is conducive to electrolyte infiltration and liquid phase transmission, and at the same time improves the compaction density of the electrode, and finally obtains a thick electrode structure with excellent energy density and rate performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries and relates to a thick lithium iron phosphate electrode and a preparation method and application thereof. Background Art

[0002] With the rapid development of new energy electric vehicles, people's demand for high-energy, high-power and high-safety power batteries continues to increase. At present, the development strategies of high-energy-density lithium batteries mainly include the development of high-capacity positive and negative electrode materials, high-voltage electrolyte introduction and thick electrode technology. Among them, thick electrode technology is the simplest and most effective way to improve battery energy density. However, with the increase of electrode thickness, the electrode peeling force is significantly reduced, the ion liquid phase transmission path is significantly increased, and the capacity decays rapidly during high-rate charge and discharge. In order to improve the kinetic performance of thick electrodes, the electrode structure can be designed and optimized from the following aspects: ① Reduce the particle size of the active main material. As the particle size decreases, the solid phase diffusion and interface reaction rates are significantly improved, and the rate performance is significantly improved; ② Electrode pore making, using mechanical pore making, chemical pore making or laser pore making methods to obtain thick electrodes with array pore structures. As the vertical pores increase, the electrode liquid phase resistance is significantly reduced, thereby improving the rate performance; ③ High-conductivity electrolyte application development, by adjusting the solvent and lithium salt composition, improving the electrolyte conductivity and reducing the electrolyte viscosity, the battery kinetic performance is improved.

[0003] However, in the actual battery development process, the use of smaller particle main materials has low compaction density and large liquid phase resistance. At the same time, the larger specific surface area leads to increased side reactions. Therefore, it is difficult to be compatible with high capacity and high rate performance when preparing thick electrodes. The use of electrode pore-making methods also has problems such as low production efficiency, large equipment investment, active material structure destruction, and battery self-discharge verification. The development of high-conductivity electrolytes faces problems such as long development cycles, limited improvement in battery kinetics, and deterioration of cycle life.

[0004] CN110010900A discloses a thick electrode with good electrochemical performance. The patent uses two electrode films with different porosities to press together, and then press the composite electrode film on a carbon-coated aluminum foil. It is made by pressing two dry electrode films. However, the invention uses two electrode films with different porosities to press together, and then press the composite electrode film on a carbon-coated aluminum foil. Since it is made by pressing two dry electrode films, there must be an interface where two electrode films are attached inside the electrode film. This kind of electrode film interface is easy to be delaminated and fall off due to the change of internal stress of the electrode during the charge and discharge process of the battery, which affects the cycle performance of the battery and the cost will also be high.

[0005] CN102324493A discloses a thick electrode with good electrochemical performance. The electrode membrane and the current collector are composited by slurry coating, dried and rolled, and then the slurry is coated on the surface of the dried electrode membrane for a second time, and the thick electrode is dried and rolled again. By controlling the pressure strength of the two rolls, it is ensured that the electrode membranes at different positions have different conductivity and porosity, which solves the problem of difficult electron and ion transmission in thick electrodes. However, the invention uses slurry coating to composite the electrode membrane with the current collector and the electrode membrane. Since the wet slurry is coated on the surface of the dried electrode membrane, it is inevitable that the dried material will dissolve again, affecting the electrode electronic conductivity and pore distribution. At the same time, the method involves two coatings, drying and rolling processes, which are cumbersome to operate and have high process energy consumption.

[0006] Therefore, how to improve the energy density and rate performance of thick lithium iron phosphate electrodes and improve the peeling strength and dynamic performance of thick electrodes is a technical problem that needs to be solved urgently. Summary of the invention

[0007] The purpose of the present invention is to provide a thick lithium iron phosphate electrode and a preparation method and application thereof. The present invention uses a layered structure of upper lithium iron phosphate secondary particles and lower lithium iron phosphate single particles (the upper layer is far away from the current collector) by matching the active materials in the first coating and the second coating, which significantly reduces the tortuosity and liquid phase resistance, and forms larger pores between the spherical secondary particles and smaller pores between the single particles, which is conducive to electrolyte infiltration and liquid phase transmission, and also improves the compaction density of the electrode, and finally obtains a thick electrode structure with excellent energy density and rate performance.

[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a lithium iron phosphate thick electrode, comprising a current collector and an electrode coating located on the surface of the current collector, wherein the electrode coating comprises a first coating and a second coating arranged in a stacked manner, wherein the second coating is located on a side close to the current collector, the first coating comprises spherical lithium iron phosphate secondary particles, a first conductive agent and a first binder, and the second coating comprises a single lithium iron phosphate particle, a second conductive agent and a second binder.

[0010] The electrode coating referred to in the present invention may be on only one side of the current collector or on both sides of the current collector.

[0011] The spherical lithium iron phosphate secondary particles provided by the present invention are formed by the accumulation and agglomeration of lithium iron phosphate primary particles.

[0012] The present invention significantly reduces the tortuosity and liquid phase resistance by matching the active materials in the first coating and the second coating and adopting a layered structure of upper lithium iron phosphate secondary particles and lower lithium iron phosphate single particles. Larger pores are formed between the spherical secondary particles, and smaller pores are formed between the single particles, which is beneficial to electrolyte infiltration and liquid phase transmission. At the same time, the compaction density of the electrode is also improved, and finally a thick electrode structure with relatively excellent energy density and rate performance is obtained.

[0013] In the present invention, if the first coating layer and the second coating layer are both single lithium iron phosphate particles, it is difficult to achieve the preparation of low tortuosity and high power density batteries. If both are secondary lithium iron phosphate particles, it will lead to problems such as low compaction density and low energy density. At the same time, if the first coating layer is single lithium iron phosphate particles and the second coating layer is spherical lithium iron phosphate secondary particles, the purpose of reducing the tortuosity of the thick electrode and improving the rate performance of the thick electrode cannot be achieved.

[0014] Preferably, the thickness of the electrode coating is 100-1000 μm, for example, 100 μm, 200 μm, 300 μm, 400 μm, 500 μm, 600 μm, 700 μm, 800 μm, 900 μm or 1000 μm.

[0015] Preferably, the thickness of the first coating accounts for 30-70% of the thickness of the electrode coating, for example, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65% or 70%, etc.

[0016] In the present invention, if the thickness of the first coating accounts for too large a proportion, it will be unfavorable for improving the energy density, while if the proportion is too small, problems such as high tortuosity of the thick electrode, poor wettability of the electrolyte, and poor rate performance will occur.

[0017] Preferably, the primary particles in the spherical lithium iron phosphate secondary particles in the first coating layer and the lithium iron phosphate single particles in the second coating layer are both nanometer-sized particles.

[0018] In the present invention, the primary particles in the secondary particles and the single lithium iron phosphate particles are all at the nanometer scale, which can better realize the rapid solid-phase diffusion of lithium ions and improve the thick electrode rate and low-temperature charge and discharge performance.

[0019] Preferably, the D50 of the spherical lithium iron phosphate secondary particles is 5 to 15 μm, for example, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm or 15 μm.

[0020] Preferably, the D50 of the primary particles in the spherical lithium iron phosphate secondary particles is 100-250 nm, for example, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, 200 nm, 210 nm, 220 nm, 230 nm, 240 nm or 250 nm.

[0021] In the present invention, if the D50 of the primary particles in the spherical lithium iron phosphate secondary particles is too large, it will lead to a slow solid phase diffusion rate of the secondary particles and a high internal resistance of the electrode, thereby affecting the rate performance and cycle stability of the thick electrode. If it is too small, the secondary particles will have a high specific surface area and a low tap density, which is not conducive to improving the compaction density of the thick electrode and improving the cycle performance.

[0022] Preferably, the first conductive agent is a composite conductive agent.

[0023] Preferably, the composite conductive agent comprises conductive carbon black and carbon nanotubes;

[0024] Preferably, the mass ratio of the carbon nanotubes to the conductive carbon black is (1-4):1, for example, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1 or 4:1.

[0025] In the present invention, in the first coating, lithium iron phosphate secondary particles are selected and matched with a composite conductive agent to form an excellent three-dimensional conductive network, which is beneficial to reducing the impedance of the thick electrode and improving the rate of charge and discharge. However, if it is matched with a separate conductive agent, such as directly matching with conductive carbon black, it will affect the electronic conductivity of the thick electrode and the liquid phase ion conductivity rate, which is not conducive to improving the rate performance of the thick electrode.

[0026] Preferably, the D50 of the lithium iron phosphate single particle is 200-800 nm, for example, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, 550 nm, 600 nm, 650 nm, 700 nm, 750 nm or 800 nm.

[0027] In the present invention, if the D50 of a single lithium iron phosphate particle is too small, it is not conducive to the liquid phase transmission of the electrolyte and the improvement of energy density. If it is too large, it will lead to a low solid phase diffusion rate of lithium ions and severe concentration polarization during charging and discharging, thereby significantly reducing the battery capacity and cycle life.

[0028] Preferably, the surface of the single lithium iron phosphate particle is coated with a carbon layer.

[0029] Preferably, the second conductive agent includes conductive carbon black.

[0030] In the present invention, the first coating layer adopts a combination of secondary particles and a composite conductive agent, and the second coating layer is combined with conductive carbon black, thereby obtaining a three-dimensional conductive network on the surface layer (away from the current collector). At the same time, the bottom small particles are in close contact with the carbon black, which can also significantly reduce the battery resistance. However, if the second coating layer combines single lithium iron phosphate particles with a composite conductive agent, the liquid retention of the bottom electrolyte is reduced, the active material is difficult to fully infiltrate, the bottom active material is unevenly deintercalated, and the internal resistance of the battery is significantly increased.

[0031] Preferably, the mass proportion of the first binder in the first coating layer is 50-80% of the mass proportion of the second binder in the second coating layer, for example, 50%, 55%, 60%, 65%, 70%, 75% or 80%.

[0032] In the present invention, the binder content in the second coating is higher than that in the first coating, which can effectively reduce binder migration, improve the peeling strength of the thick lithium iron phosphate electrode, reduce electrode powdering and cracking, and improve the cycle performance. If the binder content in the two coatings is the same, it will cause the binder surface migration, the bottom binder content is low, and the thick electrode peeling force will be significantly deteriorated. If the binder content in the first coating is higher, the thick electrode peeling force cannot be effectively improved, and the electrode is prone to cracking and powdering during baking.

[0033] Preferably, in the first coating, the mass ratio of the spherical lithium iron phosphate secondary particles, the first conductive agent and the first binder is (93-97):(1.0-2.0):(1-6), for example, 93:1:6, 95:1.5:3.5, 96:1:3 or 97:2:1, etc.

[0034] Preferably, in the second coating, the mass ratio of lithium iron phosphate single particles, the second conductive agent and the second binder is (92-95):(1.0-2.0):(3-7), for example, 92:1:7, 93:1:6, 95:1.5:3.5 or 95:2:3, etc.

[0035] In a second aspect, the present invention provides a method for preparing the lithium iron phosphate thick electrode as described in the first aspect, the preparation method comprising the following steps:

[0036] Applying the first coating slurry and the second coating slurry on the surface of the current collector so that the second coating slurry is in direct contact with the surface of the current collector and the first coating is located on the surface of the second coating, thereby obtaining the lithium iron phosphate thick electrode;

[0037] The first coating slurry includes spherical lithium iron phosphate secondary particles, a first conductive agent, a first binder and a first solvent, and the second coating slurry includes lithium iron phosphate single particles, a second conductive agent, a second binder and a second solvent.

[0038] Preferably, the coating method comprises double-layer simultaneous coating.

[0039] In the present invention, double-layer simultaneous coating refers to the synchronous coating of the first coating layer and the second coating layer. The synchronous coating method can better achieve the efficient production and coating uniformity of the lithium iron phosphate thick electrode.

[0040] Preferably, the coating is followed by drying and rolling.

[0041] Preferably, the total compaction density of the first coating and the second coating after rolling is 2.2 to 2.6 g / cc, for example, 2.2 g / cc, 2.25 g / cc, 2.3 g / cc, 2.35 g / cc, 2.4 g / cc, 2.45 g / cc, 2.5 g / cc, 2.55 g / cc or 2.6 g / cc.

[0042] In a third aspect, the present invention further provides a lithium ion battery, wherein the lithium ion battery comprises the lithium iron phosphate thick electrode as described in the first aspect.

[0043] Compared with the prior art, the present invention has the following beneficial effects:

[0044] The present invention significantly reduces the tortuosity and liquid phase resistance by matching the active materials in the first coating and the second coating, and adopts a layered structure of upper lithium iron phosphate secondary particles and lower lithium iron phosphate single particles. Larger pores are formed between the spherical secondary particles, and smaller pores are formed between the single particles, which is beneficial to electrolyte infiltration and liquid phase transmission, while also improving the compaction density of the electrode. A three-dimensional conductive network structure is obtained by matching the secondary particles with a composite conductive agent, and the single particles with a single conductive agent, which effectively reduces the internal resistance of the battery. At the same time, the coating in the thick electrode has a high peeling strength and is not easy to shed or crack, ultimately obtaining a thick electrode structure with relatively excellent energy density and rate performance. After the battery uses the thick electrode provided by the present invention, the 1C / 0.2C discharge capacity ratio can reach more than 88.6%, and the energy density can reach more than 175.2Wh / kg. After further regulating the D50 of the primary particles in the lithium iron phosphate secondary particles and the single lithium iron phosphate particles within the preferred range, the 1C / 0.2C discharge capacity ratio can reach more than 90.2%, and the energy density can reach more than 180.3Wh / kg. After further regulating the conductive agent in the coating within the preferred range of the present invention, the 1C / 0.2C discharge capacity ratio can reach more than 91.2%, and the energy density can reach more than 185Wh / kg. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 This is a schematic diagram of the structure of the lithium iron phosphate thick electrode provided in Example 1.

[0046] Figure 2 This is a SEM image of the spherical lithium iron phosphate secondary particles provided in Example 1.

[0047] Figure 3 This is a SEM image of a single lithium iron phosphate particle provided in Example 1.

[0048] Figure 4 A histogram comparison of the electrode stripping agents for thick electrodes provided in Example 1-5 and Comparative Example 1-2.

[0049] Figure 5 A comparison chart of the rate performance of the batteries provided in Examples 1-5 and Comparative Examples 1-2.

[0050] Among them, 1 is a first coating layer, 2 is a second coating layer, 3 is a current collector, 11 is a spherical lithium iron phosphate secondary particle, 12, 13 is a first conductive agent, 21 is a single lithium iron phosphate particle, and 22 is a second conductive agent. DETAILED DESCRIPTION

[0051] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0052] Example 1

[0053] This embodiment provides a lithium iron phosphate thick electrode, such as Figure 1 As shown (the structure of the single side of the current collector), the lithium iron phosphate thick electrode is composed of a current collector 3 and an electrode coating located on both sides of the current collector 3 (the thickness of the electrode coating on one side is 200 μm), the electrode coating is composed of a first coating 1 and a second coating 2 stacked in layers (the thickness of the first coating 1 is 70% of the thickness of the electrode coating), wherein the second coating 2 is in direct contact with the surface of the current collector 3, the first coating 1 is composed of spherical lithium iron phosphate secondary particles 11, a first conductive agent (12, 13) and a first binder, and the second coating 2 is composed of a lithium iron phosphate single particle 21, a second conductive agent 22 and a second binder;

[0054] The preparation method of the thick electrode is as follows:

[0055] Prepare the first coating slurry: Spherical lithium iron phosphate secondary particles (such as Figure 2 As shown, the D50 of the secondary particles is 10 μm, wherein the D50 of the primary particles is 150 nm), a first conductive agent (the mass ratio of carbon nanotubes and carbon black is 6:4) and a first binder (PVDF) are mixed, and then NMP is added and stirred to obtain a first coating slurry, wherein the mass ratio of LFP: (CNT + SP): PVDF is 94:2.0:4;

[0056] Prepare the second coating slurry: Place lithium iron phosphate single particles (such as Figure 3As shown, D50 is 300nm, the surface carbon coating amount is 1.5%), a second conductive agent (conductive carbon black) and a second binder (polyvinylidene fluoride) are mixed, and then NMP is added and stirred to obtain a second coating slurry, wherein the mass ratio of LFP:SP:PVDF is 93.5:1.5:5;

[0057] The first coating slurry and the second coating slurry are coated on the surface of the aluminum foil in a synchronous coating manner (the electrode coating is applied to the surfaces of the opposite sides of the aluminum foil), and the second coating slurry is directly located on the surface of the aluminum foil. After drying and rolling, a lithium iron phosphate thick electrode with a compaction density of 2.35 g / cc of the electrode coating on one side of the aluminum foil is obtained.

[0058] Example 2

[0059] The present embodiment provides a lithium iron phosphate thick electrode, which is composed of a current collector and an electrode coating located on both sides of the current collector (the thickness of the electrode coating on one side is 200 μm), the electrode coating is composed of a first coating and a second coating that are stacked (the thickness of the first coating is 70% of the thickness of the electrode coating), wherein the second coating is directly in contact with the surface of the current collector, the first coating is composed of spherical lithium iron phosphate secondary particles, a first conductive agent and a first binder, and the second coating is composed of a single lithium iron phosphate particle, a second conductive agent and a second binder;

[0060] The preparation method of the thick electrode is as follows:

[0061] Prepare a first coating slurry: mix spherical lithium iron phosphate secondary particles (the D50 of the secondary particles is 10 μm, and the D50 of the primary particles is 150 nm), a first conductive agent (the mass ratio of carbon nanotubes and carbon black is 6:4) and a first binder (PVDF), then add NMP and stir to obtain a first coating slurry, wherein the mass ratio of LFP: (CNT + SP): PVDF is 95: 1.5: 3.5;

[0062] Preparation of the second coating slurry: mixing lithium iron phosphate single particles (D50 of 300 nm, surface carbon coating of 1.5%), a second conductive agent (conductive carbon black) and a second binder (polyvinylidene fluoride), and then adding NMP and stirring to obtain a second coating slurry, wherein the mass ratio of LFP:SP:PVDF is 93.5:1.5:5;

[0063] The first coating slurry and the second coating slurry are coated on the surface of the aluminum foil in a synchronous coating manner (the electrode coating is applied to the surfaces of the opposite sides of the aluminum foil), and the second coating slurry is directly located on the surface of the aluminum foil. After drying and rolling, a lithium iron phosphate thick electrode with a compaction density of 2.35 g / cc of the electrode coating on one side of the aluminum foil is obtained.

[0064] Example 3

[0065] The present embodiment provides a lithium iron phosphate thick electrode, which is composed of a current collector and an electrode coating located on both sides of the current collector (the thickness of the electrode coating on one side is 400 μm), the electrode coating is composed of a first coating and a second coating that are stacked (the thickness of the first coating is 50% of the thickness of the electrode coating), wherein the second coating is directly in contact with the surface of the current collector, the first coating is composed of spherical lithium iron phosphate secondary particles, a first conductive agent and a first binder, and the second coating is composed of a single lithium iron phosphate particle, a second conductive agent and a second binder;

[0066] The preparation method of the thick electrode is as follows:

[0067] Prepare a first coating slurry: mix spherical lithium iron phosphate secondary particles (the D50 of the secondary particles is 10 μm, and the D50 of the primary particles is 150 nm), a first conductive agent (the mass ratio of carbon nanotubes and carbon black is 6:4) and a first binder (PVDF), then add NMP and stir to obtain a first coating slurry, wherein the mass ratio of LFP: (CNT + SP): PVDF is 95: 1.5: 3.5;

[0068] Preparation of the second coating slurry: mixing lithium iron phosphate single particles (D50 of 300 nm, surface carbon coating of 1.5%), a second conductive agent (conductive carbon black) and a second binder (polyvinylidene fluoride), and then adding NMP and stirring to obtain a second coating slurry, wherein the mass ratio of LFP:SP:PVDF is 93.5:1.5:5;

[0069] The first coating slurry and the second coating slurry are coated on the surface of the aluminum foil in a synchronous coating manner (the electrode coating is applied to the surfaces of the opposite sides of the aluminum foil), and the second coating slurry is directly located on the surface of the aluminum foil. After drying and rolling, a lithium iron phosphate thick electrode with a compaction density of 2.35 g / cc of the electrode coating on one side of the aluminum foil is obtained.

[0070] Example 4

[0071] The present embodiment provides a lithium iron phosphate thick electrode, which is composed of a current collector and an electrode coating located on both sides of the current collector (the thickness of the electrode coating on one side is 650 μm), the electrode coating is composed of a first coating and a second coating that are stacked (the thickness of the first coating is 30% of the thickness of the electrode coating), wherein the second coating is directly in contact with the surface of the current collector, the first coating is composed of spherical lithium iron phosphate secondary particles, a first conductive agent and a first binder, and the second coating is composed of a single lithium iron phosphate particle, a second conductive agent and a second binder;

[0072] The preparation method of the thick electrode is as follows:

[0073] Prepare a first coating slurry: mix spherical lithium iron phosphate secondary particles (the D50 of the secondary particles is 15 μm, and the D50 of the primary particles is 250 nm), a first conductive agent (the mass ratio of carbon nanotubes and carbon black is 7:3) and a first binder (PVDF), then add NMP and stir to obtain a first coating slurry, wherein the mass ratio of LFP: (CNT + SP): PVDF is 95: 1.5: 3.5;

[0074] Preparing a second coating slurry: mixing lithium iron phosphate single particles (D50 of 800 nm, surface carbon coating of 1.5%), a second conductive agent (conductive carbon black) and a second binder (polyvinylidene fluoride), and then adding NMP and stirring to obtain a second coating slurry, wherein the mass ratio of LFP:SP:PVDF is 93.5:1.5:5;

[0075] The first coating slurry and the second coating slurry are coated on the surface of the aluminum foil in a synchronous coating manner (the surfaces on both sides of the aluminum foil are coated with the electrode coating), and the second coating slurry is directly located on the surface of the aluminum foil. After drying and rolling, a lithium iron phosphate thick electrode with a compaction density of 2.45 g / cc of the electrode coating on one side of the aluminum foil is obtained.

[0076] Example 5

[0077] The present embodiment provides a lithium iron phosphate thick electrode, which is composed of a current collector and an electrode coating located on both sides of the current collector (the thickness of the electrode coating on one side is 400 μm), the electrode coating is composed of a first coating and a second coating that are stacked (the thickness of the first coating is 50% of the thickness of the electrode coating), wherein the second coating is directly in contact with the surface of the current collector, the first coating is composed of spherical lithium iron phosphate secondary particles, a first conductive agent and a first binder, and the second coating is composed of a single lithium iron phosphate particle, a second conductive agent and a second binder;

[0078] The preparation method of the thick electrode is as follows:

[0079] Prepare a first coating slurry: mix spherical lithium iron phosphate secondary particles (the D50 of the secondary particles is 12 μm, and the D50 of the primary particles is 200 nm), a first conductive agent (the mass ratio of carbon nanotubes and carbon black is 7:3) and a first binder (PVDF), then add NMP and stir to obtain a first coating slurry, wherein the mass ratio of LFP: (CNT + SP): PVDF is 94:2.0:4;

[0080] Preparing a second coating slurry: mixing lithium iron phosphate single particles (D50 of 450 nm, surface carbon coating of 2%), a second conductive agent (conductive carbon black) and a second binder (polyvinylidene fluoride), and then adding NMP and stirring to obtain a second coating slurry, wherein the mass ratio of LFP:SP:PVDF is 93.5:1.5:5;

[0081] The first coating slurry and the second coating slurry are coated on the surface of the aluminum foil in a synchronous coating manner (the surfaces on both sides of the aluminum foil are coated with the electrode coating), and the second coating slurry is directly located on the surface of the aluminum foil. After drying and rolling, a lithium iron phosphate thick electrode with a compaction density of 2.5 g / cc of the electrode coating on one side of the aluminum foil is obtained.

[0082] Example 6

[0083] The difference between this embodiment and embodiment 1 is that the conductive agent in the first coating layer of this embodiment is pure conductive carbon black.

[0084] The rest of the preparation method and process are consistent with Example 1.

[0085] Example 7

[0086] The difference between this embodiment and embodiment 1 is that the conductive agent in the second coating layer of this embodiment is consistent with the conductive agent in the first coating layer (the mass ratio of carbon nanotubes to carbon black is 6:4).

[0087] The rest of the preparation method and process are consistent with Example 1.

[0088] Example 8

[0089] The difference between this embodiment and embodiment 1 is that the D50 of the primary particles of the lithium iron phosphate secondary particles in the first coating layer of this embodiment is 300 nm, and the D50 of the secondary particles is 20 μm.

[0090] The rest of the preparation methods and parameters were the same as those in Example 1.

[0091] Example 9

[0092] The difference between this embodiment and embodiment 1 is that the D50 of the lithium iron phosphate single particle in the second coating layer of this embodiment is 2 μm.

[0093] The rest of the preparation methods and parameters were the same as those in Example 1.

[0094] Comparative Example 1

[0095] In the thick electrode provided in this comparative example, the electrode coating only contains the first coating and does not contain the second coating.

[0096] In the preparation method, the second coating slurry is not prepared.

[0097] The rest of the preparation methods and parameters were the same as those in Example 1.

[0098] Comparative Example 2

[0099] In the thick electrode provided in this comparative example, the electrode coating only contains the second coating layer and does not contain the first coating layer.

[0100] In the preparation method, the preparation of the first coating slurry is not performed.

[0101] The rest of the preparation methods and parameters were the same as those in Example 1.

[0102] Figure 4 A histogram comparison of the electrode sheet stripping agents of the thick electrodes provided by Examples 1-5 and Comparative Examples 1-2 is shown. Figure 4 It can be seen that the method for preparing the lithium iron phosphate thick electrode provided by the present invention can significantly improve the peeling force of the thick electrode, inhibit the cracking of the thick electrode, and solve the defect of powder falling.

[0103] Figure 5 A comparison chart of the rate performance of the batteries provided by Examples 1-5 and Comparative Examples 1-2 is shown, Figure 5 The bar graphs of each comparison are respectively Example 1, Comparative Example 1, Example 2, Comparative Example 2, Example 3, Example 4 and Example 5 from left to right. Figure 5 It can be seen that the lithium iron phosphate thick electrode provided by the present invention significantly improves the performance of the thick electrode, and the thick electrode has a high rate discharge performance.

[0104] Comparative Example 3

[0105] The difference between this comparative example and Example 1 is that in this comparative example, the first coating layer is directly located on the surface of the current collector, that is, the stacking order of the first coating layer and the second coating layer is swapped.

[0106] The rest of the preparation methods and parameters were the same as those in Example 1.

[0107] The lithium iron phosphate thick electrode provided in Example 1-9 and Comparative Example 1-3 was used as the positive electrode, graphite was used as the negative electrode, a polyolefin separator, and a 1M LiPF6 (solvent: EC+DMC+DEC) electrolyte to obtain a 100Ah square aluminum shell full battery.

[0108] The electrochemical performance test was performed on the batteries provided in Examples 1-9 and Comparative Examples 1-3. The test conditions were 1C / 1C charge and discharge test at 25°C and within a voltage range of 2.5 to 3.65V. The results are shown in Table 1.

[0109] Table 1

[0110] 1C / 0.2C discharge capacity ratio Energy density (Wh / kg) Example 1 95.3% 185 Example 2 94.8% 184.5 Example 3 92.3% 196.5 Example 4 91.2% 201.3 Example 5 92.6% 195.4 Example 6 91.3% 182.1 Example 7 90.2% 180.3 Example 8 89.3% 179.1 Example 9 88.6% 175.2 Comparative Example 1 86.3% 174.6 Comparative Example 2 85.3% 173.5 Comparative Example 3 79.2% 165.3

[0111] From the data results of Examples 1, 6 and 7, it can be seen that the combination of a composite conductive agent in the first coating can better achieve thick electrode rate performance and energy density improvement, while the combination of a single conductive agent in the second coating is beneficial to the wetting and capacity of the underlying active material, thereby improving the battery energy density.

[0112] It can be seen from the data results of Example 1 and Example 8 that if the D50 of the primary particles in the lithium iron phosphate secondary particles is too large, the internal resistance of the battery will increase and the rate discharge capacity retention rate will decrease.

[0113] It can be seen from the data results of Example 1 and Example 9 that if the D50 of a single lithium iron phosphate particle is too large, the solid phase diffusion rate will be reduced and the rate performance will be attenuated.

[0114] From the data results of Examples 1-2 and Comparative Examples 1 and 2, it can be seen that in the lithium iron phosphate thick electrode, whether only single particles or only secondary particles are used, high rate charge and discharge and high energy density cannot be achieved.

[0115] From the data results of Example 1 and Comparative Example 3, it can be seen that if the positions of the first coating and the second coating are swapped, the electrode tortuosity and electrolyte liquid phase transport will be seriously affected, and the internal resistance of the battery will increase significantly, making it impossible to prepare high-power and high-energy density thick electrodes.

[0116] In summary, the present invention significantly reduces the tortuosity and liquid phase resistance by matching the active materials in the first coating and the second coating, and adopts a layered structure of upper lithium iron phosphate secondary particles and lower lithium iron phosphate single particles. Larger pores are formed between the spherical secondary particles, and smaller pores are formed between the single particles, which is beneficial to electrolyte infiltration and liquid phase transmission, while also improving the compaction density of the electrode. A three-dimensional conductive network structure is obtained by adopting a matching mode of secondary particles and composite conductive agents, and single particles and single conductive agents, which effectively reduces the internal resistance of the battery. At the same time, the coating in the thick electrode has a high peeling strength and is not easy to shed or crack, ultimately obtaining a thick electrode structure with excellent energy density and rate performance. After the battery uses the thick electrode provided by the present invention, the 1C / 0.2C discharge capacity ratio can reach more than 88.6%, and the energy density can reach more than 175.2Wh / kg. After further regulating the D50 of the primary particles in the lithium iron phosphate secondary particles and the single lithium iron phosphate particles within the preferred range, the 1C / 0.2C discharge capacity ratio can reach more than 90.2%, and the energy density can reach more than 180.3Wh / kg. After further regulating the conductive agent in the coating within the preferred range of the present invention, the 1C / 0.2C discharge capacity ratio can reach more than 91.2%, and the energy density can reach more than 185Wh / kg.

[0117] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A lithium iron phosphate thick electrode, characterized in that: The lithium iron phosphate thick electrode comprises a current collector and an electrode coating located on the surface of the current collector, wherein the electrode coating comprises a first coating and a second coating arranged in a stacked manner, wherein the second coating is located on a side close to the current collector, the first coating comprises spherical lithium iron phosphate secondary particles, a first conductive agent and a first binder, and the second coating comprises a single lithium iron phosphate particle, a second conductive agent and a second binder; The D50 of the spherical lithium iron phosphate secondary particles is 10 to 15 μm; The D50 of the primary particles in the spherical lithium iron phosphate secondary particles is 100 to 250 nm; The D50 of the lithium iron phosphate single particle is 200-450nm; The first conductive agent is a composite conductive agent; the composite conductive agent includes conductive carbon black and carbon nanotubes; The second conductive agent includes conductive carbon black.

2. The lithium iron phosphate thick electrode according to claim 1, characterized in that: The thickness of the electrode coating is 100-1000 μm.

3. The lithium iron phosphate thick electrode according to claim 1, characterized in that: The thickness of the first coating layer accounts for 30-70% of the thickness of the electrode coating layer.

4. The lithium iron phosphate thick electrode according to claim 1, characterized in that: The mass ratio of the carbon nanotubes to the conductive carbon black is (1-4):

1.

5. The lithium iron phosphate thick electrode according to claim 1, characterized in that: The surface of the lithium iron phosphate single particle is coated with a carbon layer.

6. The lithium iron phosphate thick electrode according to claim 1, characterized in that: The mass proportion of the first binder in the first coating layer is 50-80% of the mass proportion of the second binder in the second coating layer.

7. The lithium iron phosphate thick electrode according to claim 1, characterized in that: In the first coating layer, the mass ratio of the spherical lithium iron phosphate secondary particles, the first conductive agent and the first binder is (93-97):(1.0-2.0):(1-6).

8. The lithium iron phosphate thick electrode according to claim 1, characterized in that: In the second coating layer, the mass ratio of the lithium iron phosphate single particles, the second conductive agent and the second binder is (92-95):(1.0-2.0):(3-7).

9. A method for preparing a lithium iron phosphate thick electrode as claimed in any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: Applying the first coating slurry and the second coating slurry on the surface of the current collector so that the second coating slurry is in direct contact with the surface of the current collector and the first coating is located on the surface of the second coating, thereby obtaining the lithium iron phosphate thick electrode; The first coating slurry includes spherical lithium iron phosphate secondary particles, a first conductive agent, a first binder and a first solvent, and the second coating slurry includes lithium iron phosphate single particles, a second conductive agent, a second binder and a second solvent.

10. The method for preparing a lithium iron phosphate thick electrode according to claim 9, characterized in that: The coating method includes double-layer simultaneous coating.

11. The method for preparing a lithium iron phosphate thick electrode according to claim 9, characterized in that: After the coating, drying and rolling are performed in sequence.

12. The method for preparing a lithium iron phosphate thick electrode according to claim 11, characterized in that: The total compacted density of the first coating layer and the second coating layer after rolling is 2.2-2.6 g / cc.

13. A lithium ion battery, characterized in that: The lithium-ion battery comprises the lithium iron phosphate thick electrode as claimed in any one of claims 1 to 8.

Citation Information

Patent Citations

  • Thick electrode with good electrochemical performance and its preparation method

    CN102324493A

  • High-rate thick electrode and preparation method and application thereof

    CN110010900A

  • Preparation method of composite electrode pole piece, composite electrode pole piece and lithium ion battery

    CN114597351A